Design and implementation of a smart safety system for rental cars using IoT and e-commerce mobile app integration for IIUM community - Hazim Johari, Muhammad Zaid; Shafie, Mohamad Amir Syakirin; Zainuddin, Ahmad Anwar; Shamsudin, Abu Ubaidah; Annas, Ammar Haziq; Bharudin, Mohamad Syafiq Asyraf; Mahazir, Mohamad Nur Badri; Ahmad Razmi, Alin Nur Maisarah; Kamarul Zaman, Nur Anis Sofea; Muhammad Zahid, Nur Adlin (Penteract Technology, 2023)
Traditional car rental systems are cumbersome for both consumers and rental companies due to the manual and time-consuming nature of the process. This work proposes the integration of a car rental system using mobile app administration and IoT (accident detection system) to address this issue. The system consists of an e-commerce platform and an IoT-powered Accident Detection System. The e-commerce platform enables users to rent automobiles and make payments online, while the Accident Detection System assists car owners in identifying any incidents involving rented vehicles. A Google survey conducted among the IIUM community (consisting primarily of students and staff) revealed that 96% of users and 100% of vehicle owners are in favour of a mobile application for car rentals and the installation of an accident detection system in rental cars. Through simulation, seat belt detection and accident detection have been developed, and future include implementing real-time monitoring using IoT technology to monitor rental compliance, locate vehicles requiring maintenance, and locate stolen vehicles. The proposed system has the potential to make automobile rental services more convenient and secure.